Preoperative anxiety and its associated factors among women undergoing elective caesarean delivery: a cross-sectional study - Yewlsew Fentie; Tikuneh Yetneberk; Moges Gelaw (BMC, 2022)
Abstract Background Anxiety is a behavioral expression of tension and unpleasant emotion that arises from multifactorial dimensions that might increase the mortality of patients during anesthesia and surgery. This study aimed to verify the prevalence and associated factors of preoperative anxiety among women undergoing elective cesarean delivery. Method A cross-sectional study design was conducted on a total of 392 patients who underwent elective cesarean delivery in Debre Tabor Comprehensive Specialized Hospital, in North Central Ethiopia from October 15, 2020, to September 15, 2021. Data was collected using a validated Amsterdam questionnaire, after translating to the local language (Amharic). Descriptive statistics were expressed in percentages and presented in tables. Bivariable and multivariable logistic analyses were done to identify factors associated with preoperative anxiety. The statistical significance level was set at P < 0.05 with 95% CI. Results The overall prevalence of preoperative anxiety in women undergoing elective cesarean delivery was 67.9 [95% CI = (63.0-72.7)]. Participants who came from rural areas [AOR = 2.65; 95%CI: 1.27-5.53], farmers [AOR = 2.35; 95%CI: 1.02-5.40], participants with no previous surgical and anesthesia history [AOR = 2.91; 95%CI: 1.69-5.01], and primiparous women [AOR = 1.69; 95%CI: 1.01-2.83] were more significantly associated with preoperative anxiety. Conclusion The prevalence of preoperative anxiety among elective cesarean deliveries was found to be high. So, preoperative maternal counseling and anxiety reduction services should therefore be given top priority, particularly for those women who came from rural areas, are farmers, have no prior surgical or anesthetic experience, and are primiparous.